Exploring the corrosion mechanism of oxide glasses using advanced solid-state nuclear magnetic resonance spectroscopy - Wang, Renle; Hu, Lili; Xu, Yongchun; Chen, Shubin; Ren, Jinjun (Acta materialia, 2024)
Despite over 70 years of study, the mechanism of glass corrosion, particularly the formation of the amorphous alteration layer known as the gel layer, remains a subject of controversy. A critical debate revolves around the origin of the abrupt change in chemical concentration near the interface between the gel layer and the glass phase. The prevailing concept attributes this shift to the dissolution of glass compositions, followed by their precipitation onto the glass surface, ultimately forming the gel layer. In this study, we utilized state-of-the-art solid-state nuclear magnetic resonance (SSNMR) techniques to track the atomic-scale network evolution of phosphate glass and borosilicate glass during corrosion. The SSNMR results demonstrate that water partially disrupts the glass network at the surface but hardly disrupts the glass network of the hydrated glass phase. This distinct interaction leads to different structures at the surface compared to the hydrated glass phase. A significant exchange of alkali metal ions in the glass occurs with H species (H+ or H3O+) in the surrounding water. Our findings demonstrate that the ion-selective diffusion, combined with the structural difference between the gel layer and hydrated glass phase, rather than the dissolution-reprecipitation of glass compositions, is responsible for the formation of a gel layer on the glass surface and the abrupt change in chemical concentration near the interface between the gel layer and the hydrated glass phase. These new findings provide valuable and novel insights into the corrosion mechanism of oxide glasses. [Display omitted]